The Public Procurement Reforms in Nigeria: Implementation and Compliance Challenges - Jibrin, Musa Success; Ejura, Success Blessing; Augustine, Nwaorgu Innocent (Journal of Asian Business Strategy, 2014)
The public procurement in Nigeria has come to stay. The problem now is not the lack of a regulatory framework but rather that of poor implementation and non-compliance with the reforms laws and regulations. This position paper made used of published data on the extent of implementation and compliance with the Nigerian reforms regulations and those of other developing and developed countries as a basis for drawing conclusion that there has been some significant improvement on the awareness of the existence of the public procurement law but for low level of implementation and compliance. The paper identified factors as media publicity; planning, organisational culture political interference amongst others contributes both positively and negatively to public procurement implementation and compliance. The need to insulate the procurement decisions from political interference and the setting up of the National Council on Public Procurement so as to allow it discharged its legitimate roles against the current trend where the Federal Executive Council and other governmental bodies performing this role are among some of the recommendations proffered by the paper if a successful implementation and compliance with the Nigerian Public Procurement reforms will be realised.